Menthol: An underestimated anticancer agent - Zhao, Yijia; Pan, Huafeng; Liu, Wei; Liu, E.; Pang, Yaobin; Gao, Hongjin; He, Qingying; Liao, Wenhao; Yao, Yejing; Zeng, Jinhao; Guo, Jing (Frontiers in Pharmacology, 2023)
Menthol, a widely used natural, active compound, has recently been shown to have anticancer activity. Moreover, it has been found to have a promising future in the treatment of various solid tumors. Therefore, using literature from PubMed, EMBASE, Web of Science, Ovid, ScienceDirect, and China National Knowledge Infrastructure databases, the present study reviewed the anticancer activity of menthol and the underlying mechanism. Menthol has a good safety profile and exerts its anticancer activity via multiple pathways and targets. As a result, it has gained popularity for significantly inhibiting different types of cancer cells by various mechanisms such as induction of apoptosis, cell cycle arrest, disruption of tubulin polymerization, and inhibition of tumor angiogenesis. Owing to the excellent anticancer activity menthol has demonstrated, further research is warranted for developing it as a novel anticancer agent. However, there are limitations and gaps in the current research on menthol, and its antitumor mechanism has not been completely elucidated. It is expected that more basic experimental and clinical studies focusing on menthol and its derivatives will eventually help in its clinical application as a novel anticancer agent.